DICER1 regulates endometrial carcinoma invasion via histone acetylation and methylation - Li, Bilan (J Cancer, 2017)
Endometrial carcinoma (EC) is one of the most common gynecologic malignancy, but molecular mechanisms of the development and progression of EC remain unclear. Here we showed that the expression of DICER1 was negatively associated with the level of histone methylation, histone acetylation and PRC2 components SUZ12 and EZH2 in EC cells. In addition, knockdown of DICER1 significantly downregulated miR-200b and let-7i, which may then regulate their targets SUZ12 and EZH2. Furthermore, knockdown of DICER1 remarkably suppressed the expression of epithelial cell marker E-cadherin, induced the expression of mesenchymal cell marker Vimentin, and promoted the invasion of EC cells. In conclusion, our data suggest that DICER1 suppresses SUZ12 and EZH2 via affecting their upstream miRNA synthesis, and inhibits epithelial-mesenchymal transition(EMT) and invasion of EC cells via histone modification.